2018
DOI: 10.1002/jcp.26356
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and colorectal cancer

Abstract: Colorectal cancer (CRC) has become the fourth leading cause of cancer-related death in the worldwide. It is urgent to find more effective therapeutic strategies for it. Reactive oxygen species (ROS) play multiple roles in normal cellular physiology processes. Thus, a certain level of ROS is essential to keep normal cellular function. However, the accumulation of ROS shows dual roles for cells, which is mainly dependent on the concentration of ROS, the origin of the cancer cell and the activated signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 117 publications
2
111
0
Order By: Relevance
“…Many investigations have found that the ROS levels in cancer cells are significantly associated with anticancer effect including proliferation inhibition and apoptosis induction. 30,[56][57][58][59] In order to explore the effect of Re-CDs on the inhibition of cancer cells, we measured the ROS level in A375 cells after they were treated with Re-CDs, by a flow cytometer. Results are displayed in Figure 6.…”
Section: Effect Of Re-cds On Ros Generation In Cancer Cellsmentioning
confidence: 99%
“…Many investigations have found that the ROS levels in cancer cells are significantly associated with anticancer effect including proliferation inhibition and apoptosis induction. 30,[56][57][58][59] In order to explore the effect of Re-CDs on the inhibition of cancer cells, we measured the ROS level in A375 cells after they were treated with Re-CDs, by a flow cytometer. Results are displayed in Figure 6.…”
Section: Effect Of Re-cds On Ros Generation In Cancer Cellsmentioning
confidence: 99%
“…Higher than normal levels of ROS cause cell death; apoptosis, autophagy, and necrosis are the three main mechanisms that result in cell death. 66 Apoptosis can be triggered extrinsically by receptor-mediated pathways or intrinsically by mitochondria-mediated mechanisms. 67 Both intrinsic and extrinsic mechanisms are integrated to regulate cell apoptosis through mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…In TPs, the cases had a lower intake of tomato juice, apples, potatoes, bananas, strawberries, sweet potatoes, cabbages, radishes, catsup, watermelon, raisins, plums, peanuts, peaches, lemon juice, lettuce, red pepper, and soybeans than controls (p < 0.05) (Table S5). Although some epidemiological studies have reported conflicting data, there is strong mechanistic evidence for the effect of antioxidants on CRC induced by reactive oxygen species, demonstrating protective mechanisms that neutralize the production of free radicals [42][43][44].…”
Section: Discussionmentioning
confidence: 99%